Occurrence and outcome of firework-related ocular injuries in Switzerland: A descriptive retrospective study - Ferhat Turgut; Alexandra Bograd; Brida Jeltsch; Adrian Weber; Petra Schwarzer; Iulia M Ciotu; Joao Amaral; Marcel N Menke; François Thommen; Tamer Tandogan; Christoph Tappeiner (BMC Ophthalmology, 2022)
Abstract Background Firework-related ocular injuries (FWROI) are a major cause of preventable visual impairment. This study aimed to analyze the occurrence and outcome of FWROI in Switzerland. Methods This retrospective multicenter study included patients with FWROI from seven centers in Switzerland from January 2009 to August 2020. Demographic information, type of injuries, medical and surgical treatments, the best corrected visual acuity (BCVA) at baseline and end of follow-up, occurrence and type of secondary complications, and duration of hospitalization were analyzed. Results A total of 105 patients (119 eyes) with a mean age of 27.1 ± 15.9 years were included in the study (71.4% male patients; 29.5% underage). Most injuries occurred around New Year’s Eve (32.4%) and the Swiss national holiday on 1 August (60.9%). The most common anterior segment findings were conjunctival or corneal foreign bodies (58%), whereas Berlin’s edema was the most common posterior segment finding (11.4%). Globe ruptures were found in four patients. The mean BCVA in all patients at first presentation was 0.4 ± 0.8 logMAR and improved to 0.3 ± 0.8 logMAR at last follow-up. A primary surgical intervention was performed in 48 eyes (40.3%). Hospitalization directly after the trauma was necessary for 18 patients for a mean of 5.8 ± 4.1 days, and a total of 4.9 ± 7.6 follow-up visits were needed. Conclusion This study provides the first data on FWROI in Switzerland, which are helpful for further preventive and educational programs and comparisons with other countries.